2019
DOI: 10.1080/14719037.2019.1648697
|View full text |Cite
|
Sign up to set email alerts
|

From government to governance…to meta-governance: a systematic literature review

Abstract: This study aims to disentangle the concept of meta-governance by systematically reviewing 79 articles. By investigating the who, what, why, and how of metagovernance, this article paints a detailed picture of its empirical manifestation. We conclude that the literature could benefit from better conceptualization and operationalization. From the results, we define meta-governance as 'a practice by (mainly) public authorities that entails the coordination of one or more governance modes by using different instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 68 publications
(76 reference statements)
1
120
0
Order By: Relevance
“…A discipline that frequently applies an SLR to enhance the knowledge base and to provide information for policy makers and practitioners is medical science [117]. SLR papers are also published in the wider social sciences [117], business (e.g., [120]), organization theory [121], and hospitality and tourism. Out of the hundreds of SLRs in tourism, examples include reviews on innovation [122], data management [123], the resource efficiency of tourist accommodation [116], sustainable tourism in a developing country [112], networked collaboration in tourist destinations [124], networks in tourism management studies [115], gendered travel risk [118], and the effects of online reviews on tourism consumers and providers [125].…”
Section: Methodology: Systematic Literature Review On Living Labsmentioning
confidence: 99%
“…A discipline that frequently applies an SLR to enhance the knowledge base and to provide information for policy makers and practitioners is medical science [117]. SLR papers are also published in the wider social sciences [117], business (e.g., [120]), organization theory [121], and hospitality and tourism. Out of the hundreds of SLRs in tourism, examples include reviews on innovation [122], data management [123], the resource efficiency of tourist accommodation [116], sustainable tourism in a developing country [112], networked collaboration in tourist destinations [124], networks in tourism management studies [115], gendered travel risk [118], and the effects of online reviews on tourism consumers and providers [125].…”
Section: Methodology: Systematic Literature Review On Living Labsmentioning
confidence: 99%
“…Democratic institutional characteristics bring legitimacy to the central role of government especially when steering market forces and non-government actors. Coordinating collaboration between policy authorities and stakeholders can create room for the state to interfere with the natural process of decision making by involving private political interests and cliental behavior (Gjaltema et al, 2019). However, the democratic legislative process can further check and balance policy making procedures as well as the political bias of the state (Bell & Hindmoor, 2009).…”
Section: Metagovernance and State Capacity To Metagovernmentioning
confidence: 99%
“…From the literature reviewed it can be concluded that the democratic process is an essential function of metagovernance (Gjaltema et al, 2019). In this respect, metagovernance literature also discusses potential challenges to the implementation of democratic governance when fair participation of stakeholders is not included in state-led governance (Bristow, Entwistle & Martin, 2008;Evans, 2007;Gjaltema et al, 2019;Qvist, 2017;Sørensen, 2006). This, however, does not reject the central role the state has in metagoverning society.…”
Section: Journal Of Public Administration and Governancementioning
confidence: 99%
See 1 more Smart Citation
“…Who and who will be involved in writing the governing framework?" This question hints at Castells (2007; proposition on power in network arrangements, as those who determine 'the rules of inclusion and exclusion' typically determine the collaborative boundary. That is, they set the rules of engagement, the terms and conditions, the governing framework for metagovernance.…”
Section: Dynamism Without Stabilitymentioning
confidence: 99%